2019
DOI: 10.3389/fimmu.2019.00635
|View full text |Cite
|
Sign up to set email alerts
|

Oral Neutrophils Characterized: Chemotactic, Phagocytic, and Neutrophil Extracellular Trap (NET) Formation Properties

Abstract: Maintenance of oral health is in part managed by the immune-surveillance and antimicrobial functions of polymorphonuclear leukocytes (PMNs), which migrate from the circulatory system through the oral mucosal tissues as oral PMNs (oPMNs). In any microorganism-rich ecosystem, such as the oral cavity, PMNs migrate toward various exogenous chemoattractants, phagocytose bacteria, and produce neutrophil extracellular traps (NETs) to immobilize and eliminate pathogens. PMNs obtained from the circulation through venip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 63 publications
2
50
0
Order By: Relevance
“…Interestingly, this group also investigated oral neutrophils in edentulous patients and found that they expressed low levels of all three activation markers and low constitutive ROS release (20). In a recent publication, these researchers characterized oral neutrophils as terminally migrated cells and reported that oral neutrophils had lost their ability to migrate in a coordinated directional manner (21). They showed that the fMLP receptor, crucial for fMLP-mediated chemotaxis, was detectable in only half of the neutrophils, compared to blood neutrophils.…”
Section: Possible Neutrophil Subsets In Periodontal Health and Inflammentioning
confidence: 99%
“…Interestingly, this group also investigated oral neutrophils in edentulous patients and found that they expressed low levels of all three activation markers and low constitutive ROS release (20). In a recent publication, these researchers characterized oral neutrophils as terminally migrated cells and reported that oral neutrophils had lost their ability to migrate in a coordinated directional manner (21). They showed that the fMLP receptor, crucial for fMLP-mediated chemotaxis, was detectable in only half of the neutrophils, compared to blood neutrophils.…”
Section: Possible Neutrophil Subsets In Periodontal Health and Inflammentioning
confidence: 99%
“…The potential use of oPMN counts as a screening tool for periodontitis is coming at a time when research concerning the immunophysiologic characteristics of oPMNs is demonstrating the potential existence of peripheral and tissue‐resident neutrophil subsets in periodontal health and disease 12,19,72,73 . This suggests the potential of using both the quantification of oPMNs and the various peripheral and oPMN population subsets to provide even greater insight into establishing the diagnosis and grading the severity of periodontitis.…”
Section: Implications Of Using Oral Neutrophil Counts In Dentistrymentioning
confidence: 99%
“…To immobilize and kill distantly localized microorganisms, neutrophils release NETs ( 75 ). Importantly, increased NET formation by oPMN, in comparison to cPMN, was reported ( 63 ), with para-inflammatory 2 subpopulation showing significantly higher release ( 73 ). This was in line with their elevated phagocytosis.…”
Section: The Function Of Oral Neutrophils and Its Modulation By The Smentioning
confidence: 98%
“…After their release from the bone marrow, neutrophils circulate for 5–9 h and then migrate into tissues where they survive 8–16 h before they die ( 63 ). Recently, a prolonged (up to 5 days) survival of activated neutrophils in tissues has been described ( 64 , 65 ), which ensures the presence of functional neutrophils at the site of inflammation ( 66 ).…”
Section: The Life-cycle Of Oral Neutrophilsmentioning
confidence: 99%
See 1 more Smart Citation